The Impact Of Digital Transformation On The Competitiveness Of SMEs Centers In Lamongan Regency With Innovation As a Mediation Variable - Rusminah, Sani; Purnomo, Nanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Tightness competition business scale national and also international , encouraging actors business besides adopting digital is also necessary For do innovation . However , the process of digitalizing MSMEs also has complexity , challenges and risks that need to be be noticed with good . The role of innovation is very important in entering the market in the digital age. Research objectives This For analyze influence digital transformation towards Power compete , analyze influence digital transformation towards innovation , analyzing influence innovation to Power competition as well as analyze influence digital transformation towards Power competition mediated by innovation . The methods used in study This is method quantitative with taking sample using purposive sampling with obtained 150 respondents , then For analyze influence between variable use tool SEM-PLS analysis . Research results This show mark p-value influence digital transformation towards Power competition as big as 0.005 where 0.05, so reject H0 means there is influence significant between digital transformation towards Power competitiveness . p- value influence Digital transformation towards Innovation as big as 0.000 where 0.05, so reject H0 means there is influence significant between Digital transformation towards Innovation . p-value influence Innovation on Competitiveness as big as 0.001 where 0.05, so that reject H0 means there is influence significant between Innovation on Competitiveness . The p-value of the influence No direct as big as 0.030 0.05, so reject H0 means Innovation significant mediate connection between Digital Transformation towards Competitiveness.